Mosquitocidal efficacy and pharmacokinetics of single-dose ivermectin versus three-day dose regimen for malaria vector control compared with albendazole and no treatment: An open-label randomized controlled trial - Yvonne Kamau; Mercy Tuwei; Caroline Wanjiku; Kelly Ominde; Mwanajuma Ngama; Jonathan Karisa; Lawrence Babu; Martha Muturi; Mwaganyuma Mwatasa; Jane Adetifa; Charlotte Kern; Urs Duthaler; et al. (International Journal of Infectious Diseases)
Objectives: When malaria vectors consume ivermectin in a blood meal, their survival probability decreases, potentially reducing malaria transmission during mass drug administrations. However, questions remain regarding the optimal dosing. This study aimed to compare the mosquitocidal effect and pharmacokinetics of two-dose regimens of ivermectin for malaria vector control. Design: We conducted an open-label randomized control trial in Kenya, staggered in blocks with sequential intervention groups and parallel controls. Participants were randomly assigned (2:1:1:1) using computer random-sequence generation, unstratified, with one block of six pharmacokinetics-only participants (single-dose ivermectin) and six blocks of four participants (3:1 intervention vs control), to receive single-dose ivermectin (400 mcg/kg, n = 12), three daily doses (3-day regimen 300 mcg/kg, n = 6), albendazole (400 mg, n = 6), or no treatment (negative control, n = 6). Our primary outcome was Anopheles gambiae survival (time-to-event [days]) after blood feeding up to 10 days after drug administration. We also evaluated pharmacokinetics (peak plasma and capillary blood concentration, areas under the plasma and capillary blood concentration-time curve from time of last administration to time of last observation, time to reach peak plasma and capillary blood concentration, terminal elimination half-life) up to 7 days after treatment. Results: A total of 36 healthy volunteers aged 21-32 years were recruited into the study and followed up to completion, with two participants not attending the visit on day 28. All drug regimens were well-tolerated. Both regimens showed significant mosquitocidal effect in the first 7 days. At 10 days after treatment, the single dose presented superior longevity of effect (adjusted hazard ratio = 3.91; 95% confidence interval = 1.93-7.93; P <0.001) compared with the triple dose (adjusted hazard ratio = 1.79; 95% confidence interval = 0.88-3.62; P = 0.0.11). Albendazole had, overall, no mosquitocidal effect. Conclusions: It is unclear why a single dose led to increased bio-efficacy compared with a triple dose. We recommend trials investigating ivermectin mass drug administrations for malaria control to consider single-dose ivermectin. A single-dose regimen is also expected to present additional operational advantages compared with a 3-day regimen, leading to improved programmatic suitability.